Model of trigger mechanisms of SARS CoV-2 infections - Galarza, Nestor Cahui; Monge Condori, Maria De Los Angeles (International Journal of Research in Medical Sciences, 2020)
Coronavirus disease-2019, is a pandemic that is causing great loss of life and economy. Knowledge of the pathogenesis of the disease is required for the control and treatment of clinical manifestations. The aim of this review is to analyses the information on the molecular mechanisms that trigger the alterations caused by SARS-CoV-2 from published articles related to COVID-19. The onset of the COVID-19 virus infection in humans occurs when the SARS-CoV-2 S protein reaches cells containing ACE2 receptors, being mainly the upper respiratory tract, followed by the oral cavity, and in lesser frequency through the conjunctiva. Inflammation and thrombus formation in symptomatic patients have been the major cause of SARS-CoV-2 aggravation, this occurs largely due to the imbalance of regulation by diminishing ACE2 receptors, which serves to activate the regulatory axis Ang-II→ACE2→Ang-(1-7)→MAS receptor, which counteracts the negative actions caused by Ang-II. The ACE2 is also the main receiver for the SARS-CoV-2 so that it can trigger the virulence processes in the host.